Maternal health literacy and adherence to recommended ANC contact among pregnant women in Indonesian - Putri, Anggie Pradana; Irawan AM., Ady; Hanifah, Lilik; Wati, Susi Erna; Lu, Yu Ying (South East Asia Nursing Research, 2023)
Maternal health literacy (MHL) equips pregnant women to seek timely Antenatal care (ANC). Through ANC, health workers can provide education that contributes to reducing the maternal mortality rate. This research aims to investigate the relationship between MHL and adherence to recommended ANC contacts and explore how mothers experience accessing ANC. The study design was a mixed-method study. A total of 305 pregnant women with various characteristics participated in this study. Quantitative data analysis used simple linear regression, while qualitative used Collaizi's strategy. The research found a positive relationship between MHL and adherence to recommended ANC contact with R2 = 0.18; F(1, 303) = 6.533, p < 0.05. Three themes represented the phenomenon of pregnant women in carrying out ANC: 1) perceptions about ANC, 2) challenges faced by pregnant women in accessing recommended ANC contact, and 3) supporting factors in doing routine ANC contact. Pregnant women with higher MHL have higher adherence to ANC contact. Health workers and policymakers can involve the results of this research in efforts to revise or make policies related to increasing pregnant women's ANC contacts.